The receptor-like kinases BAM1 and BAM2 are required for root xylem patterning - Fan, Pengfei (Proc Natl Acad Sci U S A, 2021)
Xylem patterning in the root is established through the creation of opposing gradients of miRNAs and their targets, transcripts of the HD-ZIP III family of transcriptions factors, enabled by the cell-to-cell spread of the former. The miRNAs regulating xylem patterning, miR165/6, move through plasmodesmata, but how their trafficking is regulated remains elusive. Here, we describe that simultaneous mutation of the plasma membrane- and plasmodesmata-localized receptor-like kinases (RLKs) BARELY ANY MERISTEM (BAM) 1 and 2 or expression of the geminivirus-encoded BAM1/2-interactor C4 results in higher accumulation and broader distribution of the HD-ZIP III transcripts despite normal total accumulation of miR165/6, and ultimately causes defects in xylem patterning, which depend on the function of the aforementioned miRNA targets. Taken together, our results show that BAM1 and BAM2 are redundantly required for proper xylem patterning in the Arabidopsis root, by ensuring the proper distribution and accumulation of miR165/6-targeted transcripts.